Conservation of petroglyph stone and lithic sculptures of the Huaraz lithic park - Ancash - Gutiérrez Espinola, Donal Mauricio (2021)
This is a description of the conservation project of two litho sculptures, a monolith of the Recuay Culture and the petroglyph known worldwide as "La Piedra Isabelita", attributed to the early formative, found in Cotojirca, Mareniyoc, Jangas, Ancash. All of them currently located in the lithic park, of the Huaraz Museum, Ancash. The project was based on recommendations, principles and practice on lithic conservation. We present here the graphic-photographic documentation, diagnosis and its causes of deterioration. The registration methodology processes and technical conservation criteria are included. It focuses on the intervention of the Petroglyph Isabelita including its technical, iconographic and iconological analysis, based on the publication made by its discoverer, Lic. Víctor Ponte. Its importance is given in the contextual–ceremonial aspect of this rock, by the place where it was located. It concludes with recommendations on the place where it is currently exposed.